Introduction to spatial mapping of biomolecules by imaging mass spectrometry - Shrestha, Bindesh (Elsevier, 2021)
Imaging mass spectrometry (MS) techniques are often utilized without an understanding of their underlying principles, making it difficult for scientists to determine when and how they can exploit MS to visualize their biomolecules of interest. Introduction to Spatial Mapping of Biomolecules by Imaging Mass Spectrometry is an essential reference to help scientists determine the status and strategies of biomolecule analysis, describing its many applications for diverse classes of biomolecules. The book builds a foundation of imaging MS knowledge by introducing ionization sources, sample preparation, visualization guidelines, molecule identification, quantification, data analysis, etc. The second section contains chapters focused on case studies on analyzing a biomolecule class of molecules. Case studies include an introduction/background, and a summary of successful imaging MS studies with illustrative figures and future directions.